1999
DOI: 10.1111/j.1472-8206.1999.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to intrathecal dopamine receptor agonists in conscious DOCA‐salt hypertensive rats

Abstract: Previous studies have demonstrated that in conscious deoxycorticosterone acetate (DOCA)-salt hypertensive rats, the hypotensive action of intravenous (i.v.) bromocriptine, a selective dopamine D2 receptor agonist, was mediated partly by peripheral and partly by spinal dopamine D2 receptor stimulation, and that this effect was greater and longer-lasting than that in uninephrectomized control rats. To determine whether this amplification results partly from a putative spinal hypersensitivity phenomenon, cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…Thus, it seems most likely that systemic quinpirole stimulates spinal dopamine D 2 receptors to decrease blood pressure via withdrawal of sympathetic outflow to the vasculature. Finally, the fact that blockade of spinal dopamine D 2 receptors by intrathecally injected domperidone failed to alter the baseline mean aortic pressure values in conscious normotensive rats, agrees with the previous concept that spinal dopaminergic pathways controlling blood pressure are not activated under normal conditions, at least in Wistar rats (Lahlou et al 1990;Lahlou & Demenge 1991;Lahlou 1998Lahlou & 1999.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Thus, it seems most likely that systemic quinpirole stimulates spinal dopamine D 2 receptors to decrease blood pressure via withdrawal of sympathetic outflow to the vasculature. Finally, the fact that blockade of spinal dopamine D 2 receptors by intrathecally injected domperidone failed to alter the baseline mean aortic pressure values in conscious normotensive rats, agrees with the previous concept that spinal dopaminergic pathways controlling blood pressure are not activated under normal conditions, at least in Wistar rats (Lahlou et al 1990;Lahlou & Demenge 1991;Lahlou 1998Lahlou & 1999.…”
Section: Discussionsupporting
confidence: 76%
“…In fact, blockade of low thoracic spinal dopamine D 2 receptors by intrathecal domperidone in conscious intact rats significantly enhances the maximal pressor response to intravenous quinpirole. Diffusion of intrathecal domperidone by the circulation seems unlikely, since this antagonist, which does not cross the blood-brain barrier, was shown to counteract the cardiovascular responses to intrathecal dopamine D 2 receptor agonists (Petitjean et al 1984;Lahlou 1998Lahlou & 1999. Furthermore, diffusion of intrathecal domperidone into brain stem structures by direct central spreading also seems unlikely since it was unable to prevent the quinpirole-induced stereotyped movements, which results from activation of brain dopamine D 2 receptors (metoclopramide did block the quinpirole-induced stereotypy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is possible that a putative hypersensitivity of spinal dopamine D 2 receptors might account for the blunted tachycardiac effects of bromocriptine in deoxycorticosterone acetate-salt hypertensive rats. However, this seems also unlikely since it was recently shown that bradycardiac responses to intrathecally-administered dopamine receptors in deoxycorticosterone acetate-salt hypertensive rats did not differ significantly from those in uninephrectomized, control rats, either in magnitude or in duration (Lahlou 1999).…”
Section: Discussionmentioning
confidence: 96%